1998
DOI: 10.46429/jaupr.v82i3-4.4074
|View full text |Cite
|
Sign up to set email alerts
|

Rendimiento temprano de cinco familias de cacao en tres localidades de Puerto Rico

Abstract: Five families of Theobroma cacao L. between three and eleven years of age were evaluated for yield at Gurabo, Corozal and Yabucoa. Parents involved in the combination of the families were such well-known clones as 'Pound-7', 'Scavina (SCA)-6', 'Scavina-12', and IMC, EET and UF selections which have been widely used to produce controlled-pollinated seed in Central America and elsewhere. Eight months after transplant, the temporary shade provided by plantains was removed, and the trees were grown under full sunl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 1 publication
0
2
0
1
Order By: Relevance
“…However, high parent heterozygosis also implies phenotypic heterogeneity of the seedlings. According to Irizarry and Rivera (1998), ‘The high yielding ability attributed to controlled-pollinated seeds in cacao is confined to a few superior trees’. Some authors estimated that the hybrids with highest average yield were in fact those with higher yield variability (Enriquez et al , 1987; Lockwood et al , 2007; Paulin and Eskes, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, high parent heterozygosis also implies phenotypic heterogeneity of the seedlings. According to Irizarry and Rivera (1998), ‘The high yielding ability attributed to controlled-pollinated seeds in cacao is confined to a few superior trees’. Some authors estimated that the hybrids with highest average yield were in fact those with higher yield variability (Enriquez et al , 1987; Lockwood et al , 2007; Paulin and Eskes, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Adomako and Adu-Ampomah (2003) and Sounigo et al (2003) reported high degrees of heterogeneity in the yield of individual cacao trees in breeding trials of cacao hybrids and clones in Ghana and Côte d'Ivoire, leading to high coefficients of variation (CV) in tree yield, ranging from 26% up to 95% within families. In the progenies of five controlled hybrids in Puerto Rico, Irizarry and Rivera (1998) reported that 2 to 3% of the highest yielding trees accounted for more than 60% of the family total production.…”
Section: Introductionmentioning
confidence: 99%
“…Algunas causas del fenómeno citado lo explicó Irizarry (2012) quien detalla el proceso de urbanismo experimentado en Puerto Rico, que provocó la transformación de una sociedad rural, a una urbana. Además, Pol (2001) sostuvo que el perfil económico de Puerto Rico reflejó una reducción del sistema industrial, alto desempleo, entre otros factores.…”
Section: Introductionunclassified